2020
DOI: 10.1109/access.2020.3039167
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Modular Multiplication

Abstract: Quantum modular multiplication circuit is one of the basic quantum computation circuits which are basic functions in quantum algorithms. However, since quantum-quantum modular multipliers require a high cost reversible modular inversion routine for modular multiplication, researchers have been unable to propose a feasible quantum-quantum modular multiplier. In this paper, we proposed efficient quantum-classical modular multipliers and the first quantum-quantum modular multipliers that do not require a reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In 2020, Cho et al proposed efficient quantum multipliers over and , as shown in Fig. 7 24 . They reduced the number of quantum gates and depth by half.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Cho et al proposed efficient quantum multipliers over and , as shown in Fig. 7 24 . They reduced the number of quantum gates and depth by half.…”
Section: Preliminariesmentioning
confidence: 99%
“…A quantum-classical version of the multiplier of Jang et al 25 has depth one of the gate. Table 2 shows the quantum resources for two quantum multipliers 24 , 25 .
Figure 7 The quantum multiplier over ( gate) proposed by Cho et al 24 .
…”
Section: Preliminariesmentioning
confidence: 99%
“…In the quantum setting, the problem of reversible quantum modular multiplier has been well-studied [50,51]. It has been proved that the quantum operator…”
Section: Phase Search Through Interval Amplificationmentioning
confidence: 99%
“…This optimized quantum modular adder will be very useful for quantum operations that require a full adder over GF(2 n − 1). For example, Cho et al proposed an efficient classical quantum and quantum-quantum modular multiplication circuit over GF(2 n ) and GF(2 n − 1) [34]. Their multiplication circuit can be applied to any full adder, and they used QCLA focused on speed in their simulation.…”
Section: Quantum Modular Adder Over Gf(2 N − 1)mentioning
confidence: 99%